Structural acoustics: Structural and acoustical optimization of segment plate based shell structures - Ehrnberg, Herman; Wikström, Simon (My University, 2023)
3 This thesis aims to present a novel approach to the optimization of cassette-based shell structures covering an auditorium through a combination of acoustical and structural optimization techniques. The research is divided into three phases: theory, geometry, and design. Phase 1 focuses on the theoretical foundation of the research, including the principles of acoustics, ray tracing, evolutionary algorithmic iterations, and cassette-based shell structures. This phase provides the necessary knowledge and understanding to develop a methodology for the optimization of shell structures that incorporates both acoustic and structural considerations and aims to establish a strong theoretical foundation that informs the optimization process in subsequent phases. In Phase 2, the focus shifts to geometry optimization, where iterative optimization is conducted on the geometry of the shell structure. According to the methodology developed in Phase 1 the process involves the integration of acoustical theory, ray tracing, and evolutionary algorithmic iterations. The outcome of Phase 2 is a grasshopper component that can create an optimized auditorium design based on simple input parameters such as an approximate stage and seating area. Finally, Phase 3 focuses on the final design of the auditorium based on the results of Phase 2. Materiality and effect are of critical importance in this phase. The aim is to create a visually pleasing and functional auditorium that meets the acoustic and structural performance requirements. This project aims to add value to shell structures by integrating acoustical theory, ray tracing, and evolutionary algorithmic iterations to optimize both acoustical and structural properties. The thesis's goal is to provide a new methodology for optimizing shell structures that can be applied in various contexts, such as concert halls and theatres. The research presents a valuable contribution to the field of architectural design as well as to architectural acoustics and structural engineering by presenting a new approach to optimization that considers both acoustic and structural performance.
Keywords: Optimization; Shell-structures; Ray-tracing; Acoustics; Auditorium design